Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Question 1
Let f(x)=x3−4x2+6 and g(x)=f(−x)+4. Write a rule for g.


Sagot :

Answer

  g(x)= - x3−4x²+10

Step-by-step explanation:

hello

Let f(x)=x3−4x2+6 so    g(x)=f(−x)+4.

  g(x)=(-x)3−4(-x)²+6+4

  g(x)= - x3−4x²+10 is  a rule for g     be cause (-x)3=- x3 and (-x)²=x²

We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.